NURSING STAFF DIMENSIONING AT THE ADULT ICU OF A PUBLIC TEACHING HOSPITAL - Fabieli Borges; Cristina Daiana Bohrer; Thais Vanessa Bugs; Anair Lazzari Nicola; Nelsi Salete Tonini; João Lucas Campos de Oliveir (Universidade Federal do Paraná, 2017)
The objective was to dimension the nursing staff at an Intensive Care Unit for adults in the state of Paraná and compare it with the existing staff. Cross-sectional research using a documentary source. The data were collected during 122 uninterrupted days between June and September 2016 - concerning the sociodemographic and clinical characteristics and daily Nursing Activities Score of the patient sample (n=128); and concerning the professionals working at the sector. The collected data were subject to descriptive statistical analysis, application of an intensive care staff dimensioning equation and adjustment of the dimensioned staff to the professional category according to the new Resolution by the Brazilian Federal Nursing Council, No.543/2017. The average Nursing Activities Score at the unit was 1514.89. The comparison between the dimensioned (n=87) and the actual staff (n=60) revealed a shortage of 38 nurses and a surplus of 11 nursing technicians. The actual staff does not correspond to the need for nurses.